Notes for an iconographic reading of the artistic objects of Saint Mary Virgin in Costa Rica - Bonilla Soto, Carlos (2024)
This article provides an iconographic reading of the figure of Mary of Nazareth based on the description and contextualization of artistic objects in Costa Rica. The study uses only the first two levels of reading proposed by Panofsky (1987). First, the pre-iconographic description, as a practical experience that facilitates familiarization with the objects and the circumstances that surround them, and second, the iconographic analysis to trace the constitution of the world of images, stories and allegories that underlie artistic assets. The study join the different Marian titles seen in different plastic artistic supports, into three large categories: 1. Joyful Mary; 2. Glorious Mary and 3. Mary Sorrowful, which are associated with the narrative of the mysteries of the Rosary, and are also linked to the way in which the Marian cult developed from Divine Motherhood dogmas, the Assumption to heaven and the Mary’s compassion towards her Son`s death.